Tingkat pengetahuanmahasiswaDiploma-3 Politeknik Kesehatan Gigi Makassar mengenai proteksi radiasi foto ronsen Knowledge level about x-ray radiation protection of Makassar Dental Health Polytechnic students - Barunawaty Yunus; Wahyuni Sirajuddin (Journal of Dentomaxillofacial Science, 2013)
The development of radiological technology has provided many contributions not only in widening the science ofradiology and diagnostic capabilities, but also in radiation protection to the patient as low as possible in accordancewith the clinical need. This is an important aspect in diagnostic radiology services that need continuous attention. Thisstudy aims to determine the knowledge level of Dental Health Polytechnic Makassar on radiation protection in x-rays.With cross sectional method, the sample was students of Makassar Dental Health Polytechnic, semester II and IV. Theresults showed that the number of respondents who have a very good knowledge as much as 2.343%, good as much as22.656% category, quite good as much as 40.625 %, the poor as much as 18.75%, and the category not good as muchas 15.625%. It was concluded that knowledge about x-ray radiation protection of Dental Health Polytechnic Makassar student is still lacking.